Transmissible spongy encephalopathy (with a case report) - N. V. Shuleshova; S. V. Lovitskiy; I. S. Platonova; I. V. Dvorakovskaya; V. V. Baykov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article presents the description of a case of spongy encephalopathy diagnosed morphologically in a 54 year old female. The disease lasted for 1-2 years, and had a lethal issue. The patient had undergone both out-patient and in-patient treatment in 4 city hospitals. The final diagnosis was maid after autopsy only. Difficulties of clinical diagnosis of Kreitsfeld Jacob disease which is one of the forms of transmissible spongy encephalopathy are discussed.